2012
DOI: 10.1590/s1516-35982012000500001
|View full text |Cite
|
Sign up to set email alerts
|

Apparent and true digestibility of protein and amino acid in feedstuffs used in Nile Tilapia feed as determined by the technique of dissection

Abstract: -The objective of this study was to determine the coefficients of apparent and true digestibility of protein and amino acids of five feedstuffs (corn, wheat bran, soybean meal, corn gluten meal and fish meal) in 900 sex-reversed Nile tilapia (Oreochromis niloticus) of the Thai strain during the growth phase, with an initial weight of 315±8.45 g. A total of 750 fish were distributed according to a randomized block design (repetitions in time) into five treatments with six replicates of 25 fish each. The remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…The digestibility coefficient of threonine for soybean meal, corn gluten meal, corn flour and wheat bran values found in this study were similar to those obtained by Ribeiro et al (2011Ribeiro et al ( , 2012 for tilapia, with the ADC of threonine varying between 73.0% to 90.3%. Although silver mojarra is an omnivorous species, the digestibility coefficient of threonine for fish meal was similar to that reported by Davies et al (2009) for carnivorous marine species such as turbot, bream and European seabass, with the ADC exceeding 88%.…”
Section: Apparent Digestibility Coefficients Of Amino Acids (Adcaa)supporting
confidence: 87%
“…The digestibility coefficient of threonine for soybean meal, corn gluten meal, corn flour and wheat bran values found in this study were similar to those obtained by Ribeiro et al (2011Ribeiro et al ( , 2012 for tilapia, with the ADC of threonine varying between 73.0% to 90.3%. Although silver mojarra is an omnivorous species, the digestibility coefficient of threonine for fish meal was similar to that reported by Davies et al (2009) for carnivorous marine species such as turbot, bream and European seabass, with the ADC exceeding 88%.…”
Section: Apparent Digestibility Coefficients Of Amino Acids (Adcaa)supporting
confidence: 87%
“…The pellets were sundried, packed into labeled transparent bag and stored in a cool dry place to prevent fungal growth. Six dietary treatments of supplemental lysine+DL-methionine (g 100 gG 1 ) combinations in solvent extracted soyabean based diets (SESBD) were as follows S 1 (without supplemental lysine and DL-methionine), S 2 (0+1), S 3 (0.25+0.75), S 4 (0.5+0.5), S 5 (0.75+0.25) and S 6 (1+0).…”
Section: Feed Ingredients and Diet Preparationmentioning
confidence: 99%
“…The absorbance of the solution was determined by means of a spectrophotometer at 350 nm. Percentage of chromic oxide content in samples and digestibility coefficient was calculated as follows 1…”
Section: Digestibility Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the identification of the nutritional value through digestibility studies will reveal the efficiency and utilization capacity of these feedstuffs by animals (Adéyèmi et al, 2020). In fish, this is commonly determined by quantifying the apparent digestibility coefficient (ADC) (Ribeiro et al, 2012;Solomon et al, 2017). Details on different methodologies used in digestibility studies have been extensively reported in literature.…”
Section: Digestibility Of Feed Ingredientsmentioning
confidence: 99%